The effect of bubble nasal continuous positive airway pressure application on saliva cortisol levels in full-term neonates - Idrus, Noor Fadli; Febriani, Andi Dwi Bahagia; Alasiry, Ema (Indonesian Pediatric Society, 2024)
Background Neonates with respiratory distress are commonly treated with bubble nasal continuous positive airway pressure (nCPAP) and undergo many procedures that cause stress-induced pain. Salivary cortisol is a biomarker of alteration in the hypothalamic-pituitary-adrenal axis caused by repeated and long-term exposure to stress. Objective To analyze the effect of bubble nCPAP use on salivary cortisol levels in full-term infants. Methods This study used a one-group pre-test–post-test design to compare salivary cortisol levels before and 30 minutes after bubble nCPAP application. Salivary cortisol was measured using an ELISA method. Pain was also assessed at the same time points using the Neonatal Infant Pain Scale (NIPS) score. We included infants of 37 0/7 to 42 6/7 weeks’ gestational age with respiratory distress necessitating bubble nCPAP application. Infants with birth weight of <2,500 grams, major congenital anomalies, an APGAR score of <5 at 5 minutes, shock, and infants who had undergone surgery were excluded. Results A total of 38 subjects participated in this study. Prior to bubble nCPAP application, median cortisol levels were significantly lower (1.65 ng/mL) than after bubble nCPAP application (6.8 ng/mL) (p value?). There were no significant differences in cortisol increase based on gender, type of birth, or salivary cortisol sampling time. There were significant differences in pain level after the 30-minute nCPAP application. Conclusion An increase in cortisol levels and pain scale scores during administration of bubble nCPAP indicates a pain response in full-term neonates; therefore, this procedure should be accompanied by pain or stress management.